La clasificación de la documentación parlamentaria. el cuadro de clasificación de las cortes valencianas - Cubells Puertes, María José (Revista General de Información y Documentación, 2002)
The classification of the documents of an institution is a process which is necessary for carrying out records management. To this end the most objective and stable method is sought by studying the functions and procedures of the institution since in these are reflected the competencies ascribed to it. The result is a classification table which enables the conceptual localization of the records with a view to retrieving the information through whatever variable might be posited. This work offers a document classification corresponding to the exploitation functions, which in the Cortes Valencianas correspond to the classical functions of a parliament (legislative, budgetary, promotion and control of the government´s actions), along with others assigned by the Statute of Autonomy and the Regulations of the Cortes, in addition to the organizational activities of the various organs of the house together with the preparatory process.